Building Quality Madrasah: Integrating Competency-Based Curriculum, Transformational Leadership, and Community Empowerment - Elice, Deti; Patimah, Siti; Liriwati, Fahrina Yustia; Arafah, Abdul Latief Arung; Saputra, M Indra (JURNAL AL-TANZIM, 2025)
This study focuses on developing madrasahs to improve the quality of education by integrating three main aspects: competency-based curriculum development, transformative leadership of madrasah principals, and community empowerment. This study uses a qualitative approach with a case study design. Data collection techniques were done through in-depth interviews, participatory observation, and documentation. The data obtained were analyzed through data reduction, data presentation, and verification processes to ensure the validity of the findings. The study results indicate contextual and competency-based curriculum development helps students acquire more applicable skills. Transformative leadership of madrasah principals plays a role in creating an innovative work culture and increasing teacher motivation in the learning process. Meanwhile, community empowerment creates a more supportive and inclusive education ecosystem. Integrating these three strategies forms a more holistic and sustainable madrasah development model. The implications of this study emphasize that madrasahs need to adopt a collaborative approach to improving the quality of education. Madrasah-based education policies must consider the role of madrasah principals as transformative leaders, the relevance of the curriculum to local needs, and community involvement in the education process.